CHANGES IN THE INTESTINAL MICROFLORA IN THE BABY AND THE WAYS OF THEIR CORRECTION (World Bulletin of Public Health, 2022)
To study the effect of probiotics on the intestinal microbiocenosis of young children who are naturally and artificially fed